Inter-sectoral and multilevel coordination alone do not reduce deforestation and advance environmental justice: Why bold contestation works when collaboration fails - Ravikumar, A.; Larson, A.M.; Myers, R.; Trench, T. (SAGE Publications, 2018)
Policy makers, academics, and conservationists often posit that poor coordination between different land use sectors, and between levels of governance, as an underlying challenge for reducing deforestation and forest degradation. This paper analyzes this argument using data from interviews with over 500 respondents from government, nongovernmental organizations, private companies, local and indigenous communities, activists, and individuals involved in 35 diverse land use initiatives in three countries: Peru, Indonesia, and Mexico. We find that while there is strong evidence of widespread coordination failures between sectors and levels, more fundamental political issues preclude effective coordination. We argue that political coalitions act to oppose environmental objectives and to impede their opponents from participating in land use governance. Moreover, we find that where coordination between actors does occur, it does not necessarily produce environmentally sustainable and socially just land use outcomes. Where we do find successful initiatives to reduce deforestation and benefit local people, effective coordination between well-informed actors is often present, but it does not occur spontaneously, and is instead driven by political organizing over time by activists, local people, nongovernmental organizations, and international donors. We suggest that the global environmental community must recognize explicitly these political dimensions of land use governance in order to successfully collaborate with local people to reduce deforestation.